Предмет: Математика,
автор: mishavit47
-(3x+2)-(7-5x)=-6; -5(x-3)-(-7x-1)=2
Ответы
Автор ответа:
0
1)-(3х+2)-(7-5х)=-6
-3х-2-7+5х=-6
-3х+5х=-6+2+7
2х=3
х=1.5
2)-5(х-3)-(-7х-1)=2
-5х+15+7х+1=2
2х=2-15-1
2х=-14
х=-7
-3х-2-7+5х=-6
-3х+5х=-6+2+7
2х=3
х=1.5
2)-5(х-3)-(-7х-1)=2
-5х+15+7х+1=2
2х=2-15-1
2х=-14
х=-7
Автор ответа:
0
-(3x+2)-(7-5x)=-6
-3x-2-7+5x=-6
2x-9=-6
2x=-6+9
2x=3
x=3/2
x=1.5
-5(x-3)-(-7x-1)=2
-5x+15+7x+1=2
2x+16=2
2x=2-16
2x=-14
x=-14:2
x=-7
-3x-2-7+5x=-6
2x-9=-6
2x=-6+9
2x=3
x=3/2
x=1.5
-5(x-3)-(-7x-1)=2
-5x+15+7x+1=2
2x+16=2
2x=2-16
2x=-14
x=-14:2
x=-7
Похожие вопросы
Предмет: Геометрия,
автор: marios1994
Предмет: История,
автор: zejnabmilaha
Предмет: История,
автор: anonymous33
Предмет: Математика,
автор: нюта871
Предмет: Математика,
автор: Артем313